The Building Emotional Awareness and Mental health (BEAM) program developed with a community partner for mothers of infants: protocol for a feasibility randomized controlled trial - Kayla M. Joyce; Charlie Rioux; Anna L. MacKinnon; Laurence Y. Katz; Kristin Reynolds; Lauren E. Kelly; Terry Klassen; Tracie O. Afifi; Aislin R. Mushquash; Fiona M. Clement; Mariette Chartier; Elisabeth Bailin Xie; et al. (Pilot and Feasibility Studies, 2023)
Abstract Background Drastic increases in the rates of maternal depression and anxiety have been reported since the COVID-19 pandemic began. Most programs aim to improve maternal mental health or parenting skills separately, despite it being more effective to target both concurrently. The Building Emotional Awareness and Mental health (BEAM) program was developed to address this gap. BEAM is a mobile health program aiming to mitigate the impacts of pandemic stress on family well-being. Since many family agencies lack infrastructure and personnel to adequately treat maternal mental health concerns, a partnership will occur with Family Dynamics (a local family agency) to address this unmet need. The study’s objective is to examine the feasibility of the BEAM program when delivered with a community partner to inform a larger randomized controlled trial (RCT). Methods A pilot RCT will be conducted with mothers who have depression and/or anxiety with a child 6–18 months old living in Manitoba, Canada. Mothers will be randomized to the 10 weeks of the BEAM program or a standard of care (i.e., MoodMission). Back-end App data (collected via Google Analytics and Firebase) will be used to examine feasibility, engagement, and accessibility of the BEAM program; cost-effectiveness will also be examined. Implementation elements (e.g., maternal depression [Patient Health Questionnaire-9] and anxiety [Generalized Anxiety Disorder-7]) will be piloted to estimate the effect size and variance for future sample size calculations. Discussion In partnership with a local family agency, BEAM holds the potential to promote maternal-child health via a cost-effective and an easily accessible program designed to scale. Results will provide insight into the feasibility of the BEAM program and will inform future RCTs. Trial registration {2a} This trial was retrospectively registered with ClinicalTrial.gov ( NCT05398107 ) on May 31st, 2022.